1975
DOI: 10.1159/000158038
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Receptors of the Cerebral Arteries of the Goat

Abstract: 5-Hydroxytryptamine (5-HT), norepinephrine (NE), histamine (H) and potassium (K+) chloride induce dose-dependent changes in tension of the isolated middle cerebral artery of the goat. Vasopressin produces highly variable responses followed by tachyphylaxis; angiotensin II is ineffective over a wide dose range. The order of potencies of these vasoactive agents is 5-HT > NE > H > K+. With regard to their ability to induce maximal contractile responses, the order is: H > 5-HT, K+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

1976
1976
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
1
17
2
Order By: Relevance
“…These data also correlate with in vitro data obtained from much larger cerebral vessels in cats and goats. 15 ' 25 However, unlike Wahl et al 26 we were unable to demonstrate any dilation produced by phentolamine, hence we could not provide evidence for adrenergic tone in "resting" vessels. This may be because Wahl et al used doses 10 to 50 times greater than ours.…”
Section: Effects Of Adrenergic Blockerscontrasting
confidence: 66%
See 1 more Smart Citation
“…These data also correlate with in vitro data obtained from much larger cerebral vessels in cats and goats. 15 ' 25 However, unlike Wahl et al 26 we were unable to demonstrate any dilation produced by phentolamine, hence we could not provide evidence for adrenergic tone in "resting" vessels. This may be because Wahl et al used doses 10 to 50 times greater than ours.…”
Section: Effects Of Adrenergic Blockerscontrasting
confidence: 66%
“…• 15 Prior to our use of the image splitting-TV technique, we failed to find either a constricting or dilating effect of histamine. 16 We repeated our studies using the newer technique and the larger-sized vessels that have been the major focus since we began using the technique.…”
Section: Effects Of Histaminementioning
confidence: 95%
“…The sensitivity of cerebral vascular muscle to NE in a number of species, including the cat (Edvinsson and Owman, 1974), goat (Urquilla et al, 1975), and rabbit , is considerably less than in systemic arteries and veins of the same species. This characteristic, combined with an exceedingly dense innervation and the possibility of an endothelial as well as metabolic barriers to intraluminal NE action (McCalden et al, 1977), results in a blood vessel which, although not responsive to circulating catecholamines, is still influenced by neurogenic activity.…”
Section: Sensitivity Of A-and ^-Adrenergic Receptormediated Responsesmentioning
confidence: 95%
“…22 The function of this serotonergic innervation is unknown. Because serotonin is a powerful constrictor of major cerebral arteries, [25][26][27] one can assume that it might participate in the control of the cerebral blood flow. Thus, the neurogenic contraction elicited by electrical stimulation of isolated rat basilar artery segments was reduced in the presence of serotonergic antagonists.…”
Section: See Editorial Comment Page 1701mentioning
confidence: 99%
“…Because 5-HT is a potent constrictor agent of these blood vessels, [25][26][27] it might be expected to cause a change in cerebral blood flow according to the variations of the serotonergic tone. It has been reported that chemical or electrical stimulation of DRN induces a decrease of regional blood flow in several brain areas, 49 -51 whereas systemic administration of 8-OH-DPAT augments cerebral blood flow in different brain regions.…”
Section: Drn Serotonin Levels After Local Injection Of 5-ht (1 G) or mentioning
confidence: 99%